Plasma argon particle interactions in a non-equilibrium state through the Maxwell-Boltzmann kinetic equation - Azza Ronald; Saktioto Saktioto; Kusherbayeva Maikul; Kushkimbayeva Bibara; Mohd Rendy Samudra; Dedi Irawan; Hewa Yaseen Abdullah (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2025)
Non-thermal argon plasmas serve multiple functions, particularly in healthcare and industrial applications. Numerous particles of the same species exhibit varying velocities, referred to as a population. The distribution function is a standard method for characterizing a population. The speed and energy distribution functions in the Maxwell-Boltzmann equation are simulated utilizing MATLAB. The density of each species was numerically calculated using the Runge-Kutta method. This research reviews various argon species, including Ar*, Ar+, Ar(1s5), Ar(1s4), Ar(1s3), Ar(1s2), Ar, and electrons. The parameters utilized include a pressure of 10 mTorr, an argon temperature about 400 K, and an electron temperature about 30,000 K. The maximum velocity probability density value is observed in the Ar+ species at 6.18 × 107 (m/s)-1, while the minimum value is found in electrons at 1.93 (m/s)-1. The maximum energy probability density value is observed in the Ar+ species at 2.13 × 1029 (Joule)-1, while the minimum value is found in the Ar(1s3) species at 1.40 × 1025 (Joule)-1. The time evolution of the distribution function, independent of the coordinates r, is associated with v, at t = 10-8 s. The velocity distribution function is significantly affected by the density value, while the distribution function is contingent upon the velocity.